2023
DOI: 10.1038/s41419-023-05971-1
|View full text |Cite
|
Sign up to set email alerts
|

PTRF-IL33-ZBP1 signaling mediating macrophage necroptosis contributes to HDM-induced airway inflammation

Abstract: Polymerase 1 and transcript release factor (PTRF, encoding by Cavin-1) regulates interleukin 33 (IL-33) release, which is implicated in asthma development. Z-DNA binding protein 1 (ZBP1)-sensing Z-RNAs induces necroptosis which causes inflammatory diseases. House dust mite (HDM) is the major source of allergen in house dust and is strongly associated with the development of asthma. Whether PTRF via IL-33 and ZBP1 mediates HDM-induced macrophage necroptosis and airway inflammation remains unclear. Here, we foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In addition, recent studies have shown that the MLKL inhibitor GW806742X can block IL-33 secretion from bronchial epithelial cells both in vitro and in vivo, and can reduce eosinophilic airway inflammation in an allergic inflammation model [ 43 ]. Additionally, PTRF-IL-33-ZBP1 signaling has been found to mediate macrophage necroptosis and is involved in HDM-induced airway inflammation [ 44 ]. To date, an increasing number of studies have confirmed the important role of necroptosis in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies have shown that the MLKL inhibitor GW806742X can block IL-33 secretion from bronchial epithelial cells both in vitro and in vivo, and can reduce eosinophilic airway inflammation in an allergic inflammation model [ 43 ]. Additionally, PTRF-IL-33-ZBP1 signaling has been found to mediate macrophage necroptosis and is involved in HDM-induced airway inflammation [ 44 ]. To date, an increasing number of studies have confirmed the important role of necroptosis in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…RIPK3 is involved in activating the NLRP3 inflammasome in infiltrating macrophages in LPS‐induced ALI, and the interaction between RIPK3 and the NLRP3 inflammasome can be hindered by RIPK3 inhibitor GSK‐872 117 . Polymerase 1 and transcript release factor (PTRF) promotes IL‐33 release, with involvement in the development of asthma 118 . ZBP1‐sensing Z‐RNA evokes necroptosis, contributing to inflammatory diseases 119 .…”
Section: The Key Molecular Mechanisms Underlying Necroptosis Of Speci...mentioning
confidence: 99%
“…House dust mite (HDM) remains the dominating source of allergen in house dust, which is notably connected to asthma. PTRF mediates ZBP1‐mediated necroptosis of macrophages and airway inflammation, which can be enhanced by bronchial epithelial cell‐released IL‐33 118 (Figure 5). Aside from pyroptosis, 120 RSV infection elicits RIPK1‐, RIPK3‐, and MLKL‐based necroptosis in alveolar macrophages 121 .…”
Section: The Key Molecular Mechanisms Underlying Necroptosis Of Speci...mentioning
confidence: 99%